A performance comparison of PID and Fuzzy Logic Control methods for trajectory tracking of wheeled mobile robot - Aminurrashid, Noordin (Universiti Malaysia Perlis (UniMAP), 2022)
Link to publisher's homepage at http://ijneam.unimap.edu.my